The Influence of Virtual Reality on Consumer Decision-Making in Purchasing Maybelline Products - Najiatun; Jannatul Firdaus (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid development of immersive technologies such as virtual reality has reshaped consumer behavior and marketing strategies by offering interactive experiences that influence perceptions and purchasing decisions. This study aims to analyze and understand the influence of virtual reality on the consumer decision-making process, with a focus on a case study of purchasing. Maybelline cosmetic products. With the rapid development of digital technology, virtual reality has emerged as an innovative marketing tool that offers interactive and immersive experiences for consumers. The research method used is a quantitative approach, with data analysis used in this study using the SEM-AMOS method. The population in this study is active e-commerce consumers and virtual reality users. The data collection used questionnaires distributed to 200 e-commerce consumers and virtual reality users aged 18–40 years, selected through purposive sampling. Interactive experiences have a stronger and more strategic role than visual experiences in influencing consumer interest through actual behavior. The results showed that interactive experiences through virtual reality had a stronger influence on consumer interest and purchase intention compared to purely visual experiences. This study concludes that while visual elements serve as an initial attraction, interactive experiences are more effective in fostering engagement and transforming consumer behavior.